Star Anise Reverses Benzopyrene-Induced Immune Dysfunction in Rats: Adas bintang Membalikkan Disfungsi Kekebalan Tubuh yang Diinduksi Benzopiren pada Tikus - Saleh, Eman Naji; Saeed, Iktefa Abdul Hamid Mohammed; latef, Nedhal ibrahim (Academia Open, 2024)
Background: Benzopyrene (B[a]P), a polycyclic aromatic hydrocarbon, is known for its carcinogenic and immunotoxic effects, posing significant health risks upon exposure. Specific Background: Despite numerous studies, effective therapeutic strategies to mitigate B[a]P-induced toxicity remain limited. Star anise, a medicinal plant with anti-inflammatory properties, holds potential as a protective agent against such toxicity. Knowledge Gap: The impact of star anise on B[a]P-induced immunotoxicity, particularly on hematological parameters, has not been thoroughly investigated. Aims: This study aimed to explore the effects of B[a]P intoxication and its treatment with star anise on hematological parameters in rats. Methods: Thirty male Sprague Dawley rats were divided into six groups: Control, B[a]P, and varying doses of star anise (125 mg/kg, 120 mg/kg + B[a]P, 125 mg/kg + B[a]P, 130 mg/kg + B[a]P). Blood samples were analyzed using an auto blood analyzer. Results: While erythrogram parameters showed no significant differences among groups, B[a]P exposure significantly increased WBC parameters (Mid, Gran, L, and total WBC counts), indicating an inflammatory and immunosuppressive response. Treatment with star anise significantly reduced these parameters, suggesting its protective effects. Novelty: This study is the first to demonstrate the efficacy of star anise in mitigating B[a]P-induced leukocytosis and immune toxicity in rats. Implications: These findings highlight the potential of star anise as a therapeutic agent against B[a]P-induced immunotoxicity, warranting further investigation into its clinical applications. Highlights: Benzopyrene Exposure: Increases WBC parameters, indicating immune response. Star Anise Treatment: Reduces WBC counts, showing protective effects. Novel Findings: Star anise mitigates B[a]P-induced immunotoxicity in rats. Keywords: Benzopyrene, Star Anise, Hematological Parameters, Immunotoxicity, Rats